EPR Spectroscopy Coupled with Spin Trapping as an Alternative Tool to Assess and Compare the Oxidative Stability of Vegetable Oils for Cosmetics - Giulia Di Prima; Viviana De Caro; Cinzia Cardamone; Giuseppa Oliveri; Maria Cristina D’Oca (Applied Sciences)
Antioxidants are the most popular active ingredients in anti-aging cosmetics as they can restore the physiological radical balance and counteract the photoaging process. Instead of adding pure compounds into the formulations, some “precious” vegetable oils could be used due to their content of tocopherols, phenols, vitamins, etc., constituting a powerful antioxidant unsaponifiable fraction. Here, electron paramagnetic resonance (EPR) spectroscopy coupled with spin trapping was proven to provide a valid method for evaluating the antioxidant properties and the oxidative resistance of vegetable oils which, following UV irradiation, produce highly reactive radical species although hardly detectable. Extra virgin olive oil, sweet almond oil, apricot kernel oil, and jojoba oil were then evaluated by using N-t-butyl-α-phenylnitrone as a spin trapper and testing different UV irradiation times followed by incubation for 5 to 180 min at 70 °C. The EPR spectra were manipulated to obtain quantitative information useful for comparing the different tested samples. As a result, the knowledge acquired via the EPR analyses demonstrated jojoba oil as the best of the four considered oils in terms of both starting antioxidant ability and oxidative stability overtime. The obtained results confirmed the usefulness of the EPR spin trapping technique for the main proposed purpose.